Composição dos Óleos Essenciais de Anis-estrelado Illicium verum L. e de Capim-limão Cymbopogon citratus (DC.) Stapf: Avaliação do Efeito Repelente sobre Brevicoryne brassicae (L.) (Hemiptera: Aphididae) - Lima, Rafaela; Cardoso, Maria das Graças; Moraes, Jair; Vieira, Sara; Melo, Bruno; Filgueiras, Camila (BioAssay, 2009)
Plants produce a variety of compounds via the secondary metabolism that are related to the interaction of the plant with the environment, such as defense against insects, bacteria and fungi. The essential oils constitute a type of secondary metabolite of great economic importance, being increasingly studied and utilized together with the integrated management of pests. Thus, the present study proposed to investigate the effects of the essential oil from the Japanese star anise (Illicium verum L.) and from lemon grass (Cymbopogon citratus) leaves on the behavior of the kale aphid Brevicoryne brassicae (L.). The essential oils were obtained by steam distillation and analyzed by gas chromatography and by gas chromatography coupled with mass spectrometry. The preference test with choice was preformed with five treatments. Three treatments utilized 0.05; 0.1 and 0.5% concentrations of the essential oil from I. verum and 0.1; 0.05 and 0.01% concentrations of the essential oil from C. citratus diluted in 1:1 acetone:water. Two controls were used, one with water and the other with 1:1 acetone:water. The preference of the aphids was observed at 24 and at 48 h after initiating the experiments. The essential oils from I. verum and C. citratus presented repellent/deterrent effects for the kale aphid at concentrations of 0.5% and 0.1%, respectively.